Chronic central nervous system aspergillosis with coexisting GFAP and AQP4 antibody positivity: case report and literature review - Cao, Yimin; Zhao, Xueying; Hao, Shengpu; Yang, Haiqing; Gao, Duo; Du, Shixuan; Wang, Liang; Zhou, LiXia (Frontiers in Immunology, 2025)
This article presents an unusual case of chronic central nervous system (CNS) aspergillosis with concurrent glial fibrillary acidic protein (GFAP)-IgG and aquaporin-4 (AQP4)-IgG seropositivity. The patient presented with progressive numbness and weakness of the extremities over three months. The diagnosis was established by a cell-based assay demonstrating double positivity for GFAP-IgG and AQP4-IgG; imaging revealed multiple foci in the right temporo-occipital lobe and cervical medulla. Surgical pathology confirmed parenchymal Aspergillus infection. Postoperative treatment with voriconazole was effective. This case represents, to our knowledge, the first report of chronic CNS aspergillosis with concurrent GFAP-IgG and AQP4-IgG positivity. These findings suggest that chronic fungal infections may induce multiple distinct antibody responses, thereby offering new insights into the mechanisms linking infection and immunity. Clinical vigilance is therefore warranted for the development of autoimmune antibodies following chronic fungal infections, and an early diagnosis may be facilitated by integrating clinical, imaging, and pathological evaluations.